2011
DOI: 10.1590/s0100-69162011000400013
|View full text |Cite
|
Sign up to set email alerts
|

Estratégias de aeração de milho armazenado: temperatura e teor de água

Abstract: RESUMO:O objetivo deste trabalho consistiu em avaliar e comparar o desempenho de três diferentes estratégias de aeração de milho armazenado: aeração contínua, aeração noturna e aeração em condições de equilíbrio higroscópico entre os grãos e o ar ambiente. Utilizaram-se grãos de milho com dois níveis de teor de água; 11% e 17%. Realizou-se monitoramento contínuo da temperatura, e amostras de grãos foram retiradas durante os ensaios para análise do teor de água. Observou-se que todas as estratégias de aeração f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Thus, the fact that grains harvested with higher moisture contents have high metabolic activity could be confirmed, since the heating of the mass of grains is one of the main characteristics of the high respiratory activity (Nascimento & Queiroz, 2011).…”
Section: Resultsmentioning
confidence: 90%
“…Thus, the fact that grains harvested with higher moisture contents have high metabolic activity could be confirmed, since the heating of the mass of grains is one of the main characteristics of the high respiratory activity (Nascimento & Queiroz, 2011).…”
Section: Resultsmentioning
confidence: 90%
“…Aeration of the stored grain mass did not significantly reduce the grain mass temperature (0.5 to 1 °C) which (Cardoso et al, 2012;Quirino et al, 2013;Coradi et al, 2016b;Nascimento & Queiroz, 2016). In these conditions, it was observed that the grain deterioration process increased as a function of the water content change after equilibration with the air temperature and relative humidity ( Table 3).…”
Section: Resultsmentioning
confidence: 92%